2017
DOI: 10.1002/pat.3989
|View full text |Cite
|
Sign up to set email alerts
|

Light-triggered antifouling coatings for porous silicon optical transducers

Abstract: Nanostructured porous silicon (PSi) is an attractive platform for the design of biosensors because of its high sensitivity and selectivity towards various biological targets. Its use for biosensing applications, however, is compromised as a result of interfacial interactions with biological molecules that may accumulate on their surfaces and degrade their performance. We describe a new hybrid system comprising an oxidized PSi (PSiO2) nanostructure and antifouling (anti‐adsorption), light‐triggered pre‐polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…In another study, the size and morphology of photocross-linkable nanoparticles containing cinnamate groups were controlled for a desired time during hydrolysis by means of additional UV irradiation. 39 In a previous study, 40 we demonstrated the ability of a PEG 4 -CAA conjugate of higher molecular weight to serve as an antifouling hydrogel owing to the fact that both PEG 4 Compared with other photoresponsive molecules such as azide 41 and anthracene, 42 this system provides a simple step for synthesizing biosafe molecules without compromising stabilization efficiency, which makes fabrication more amenable to large-scale production.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In another study, the size and morphology of photocross-linkable nanoparticles containing cinnamate groups were controlled for a desired time during hydrolysis by means of additional UV irradiation. 39 In a previous study, 40 we demonstrated the ability of a PEG 4 -CAA conjugate of higher molecular weight to serve as an antifouling hydrogel owing to the fact that both PEG 4 Compared with other photoresponsive molecules such as azide 41 and anthracene, 42 this system provides a simple step for synthesizing biosafe molecules without compromising stabilization efficiency, which makes fabrication more amenable to large-scale production.…”
Section: Resultsmentioning
confidence: 94%
“…In another study, the size and morphology of photocross‐linkable nanoparticles containing cinnamate groups were controlled for a desired time during hydrolysis by means of additional UV irradiation . In a previous study, we demonstrated the ability of a PEG 4 ‐CAA conjugate of higher molecular weight to serve as an antifouling hydrogel owing to the fact that both PEG 4 and CAA have inherent antifouling properties. This light‐triggered protecting layer anchored efficiently to the silicon walls of biosensors, thus preventing fouling of proteins on them without compromising biosensor sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Stimuli responsive materials play an important role in many biomedical applications, including drug delivery, self-healing coatings, , medical adhesives, and antifouling surfaces. , These materials are capable of responding to external stimuli, such as pH, redox, enzymes, light, temperature, magnetic, and electrical signal by changing their physicochemical properties. Among these, light is of particular interest, since its parameters (distance, intensity, wavelength, etc.)…”
Section: Introductionmentioning
confidence: 99%